2013
DOI: 10.1042/an20130010
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Responses of Primary Human Astrocytes and Brain Microvascular Endothelial Cells to the Lyme Disease Spirochete, Borrelia Burgdorferi

Abstract: The vector-borne pathogen, Borrelia burgdorferi, causes a multi-system disorder including neurological complications. These neurological disorders, collectively termed neuroborreliosis, can occur in up to 15% of untreated patients. The neurological symptoms are probably a result of a glial-driven, host inflammatory response to the bacterium. However, the specific contributions of individual glial and other support cell types to the pathogenesis of neuroborreliosis are relatively unexplored. The goal of this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…The finding of neutrophil activation in both LNB and EVM is intriguing, since these infections have similarities with respect to both clinical presentation and CSF cellular profile, which may include neutrophil predominance in the early phase [35]. Several studies have de facto shown the presence of neutrophil-activating cytokines and chemokines in the CSF samples of patients with LNB [36][37][38][39] and EVM [40,41], and the production of neutrophil chemo-attractants, such as CXCL1, CXCL8 and CXCL10 after in vitro stimulation of neuronal cells in response to B. burgdorferi spirochaetes [42]. Thus, there appears to be a prerequisite for neutrophil recruitment into the CNS in infections caused by B. burgdorferi and enterovirus.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of neutrophil activation in both LNB and EVM is intriguing, since these infections have similarities with respect to both clinical presentation and CSF cellular profile, which may include neutrophil predominance in the early phase [35]. Several studies have de facto shown the presence of neutrophil-activating cytokines and chemokines in the CSF samples of patients with LNB [36][37][38][39] and EVM [40,41], and the production of neutrophil chemo-attractants, such as CXCL1, CXCL8 and CXCL10 after in vitro stimulation of neuronal cells in response to B. burgdorferi spirochaetes [42]. Thus, there appears to be a prerequisite for neutrophil recruitment into the CNS in infections caused by B. burgdorferi and enterovirus.…”
Section: Discussionmentioning
confidence: 99%
“…Direct incubation of astrocytes with the gram-negative Borrelia burgdorferi up-regulated synthesis and release of the matrix metalloprotease 9, that could contribute to the disruption of the blood-brain barrier (Perides et al ., 1999). In addition, an exposure to B. burgdorferi caused an increase in the production of IL-6, TNF-α, IL-8, chemokine (C-X-C motif) ligand 1 (CXCL-1), and CXCL-10 in human cultured astrocytes (Brissette et al ., 2013). …”
Section: Infectious Diseases Of the Cnsmentioning
confidence: 99%
“…Their functions include: maintaining ion and pH homeostasis, promoting synthesis and removal of neurotransmitters, providing glucose supply and antioxidant defense, and regulating synaptic activity by producing cytokines, chemokines, growth factors, and metabolites (Choi et al, 2014;Kang et al, 2014). They also assist in tight junction formation and expression and localization of transporters (Brissette et al, 2013). They also assist in tight junction formation and expression and localization of transporters (Brissette et al, 2013).…”
Section: Astrocytesmentioning
confidence: 99%
“…Borrelia burgdorferi is the causative agent of Lyme disease, which includes meningitis among its later manifestions in 10-15% of patients (Brissette et al, 2013;Halperin, 2014). Unlike most gram-negative bacteria, B. burgdorferi does not produce LPS, which renders it immunologically distinct from other gram-negative organisms, interacting primarily via TLR 2 rather than TLR4 (Rasley et al, 2002(Rasley et al, , 2006.…”
Section: Borrelia Burgdorferimentioning
confidence: 99%
See 1 more Smart Citation